2019
DOI: 10.1016/j.cej.2018.12.136
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and photocatalytic degradation of VOCs by perfluorinated ionomeric coating with TiO2 nanopowders for air purification

Abstract: In this work, we propose a transparent multilayered perfluoropolymeric coating as immobilization method for TiO2 nanoparticles, and evaluate its suitability in the gas phase photocatalytic degradation of six different volatile organic compounds. The coating was made of a layer of TiO2containing perfluorosulfonic acid polymer on a layer of perfluorinated amorphous polymer. The chemical stability of perfluoropolymeric materials to UV radiation and UV-activated TiO2 overcomes the possible degradation of the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 108 publications
(116 reference statements)
0
25
0
Order By: Relevance
“…Sansotera et al’s study [53] revealed that the increase in atmospheric humidity progressively increased the photodegradation rates of VOCs given that water vapors can be adsorbed on the TiO 2 active sites as resources for • OH, and therefore the enhancement of inactivation performance may result from the promoted generation of ·OH under high humidity [54] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sansotera et al’s study [53] revealed that the increase in atmospheric humidity progressively increased the photodegradation rates of VOCs given that water vapors can be adsorbed on the TiO 2 active sites as resources for • OH, and therefore the enhancement of inactivation performance may result from the promoted generation of ·OH under high humidity [54] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 is one the most employed semiconductors. It has found applications in water and air purification [16][17][18], sterilization [19], self-cleaning building materials [20], defogging [21], and H 2 generation from water splitting [22]. TiO 2 is cheaper and more photo-chemically and chemically stable than other semiconductors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the cell membrane of B. subtilis and its spore could protect them from the attack of ROSs during photocatalysis. The Log inactivation efficiency of the photocatalyst was increased with respect to the humidity from 30 to 95 %, indicating that the high humid conditions stimulate the photo-generation of ROSs [80] , [81] . The reactivation of microbes was tested after the treatment of photolysis and photocatalysis.…”
Section: Recent Advancesmentioning
confidence: 99%